TEORI PERSEPSI MULLÃ SHADRÃ BESERTA IMPLIKASI EPISTEMOLOGI DAN METODOLOGISNYA UNTUK PSIKOLOGI - Heriyanto, Husein (Faculty of Ushuluddin and Humanities, 2015)
Human action is seen as behavior of organisms that are subject to the law of effect (the law of effect) throughÂ the process of reinforcement and punishment, stimulus-response mechanism, learning by trial, and the laws ofÂ Biochemistry and physiological. Mullâ Shadrâ has brought us to a new consciousness that we are over this as ifÂ asleep because it doesnât realize that all our actions including sensory perception is our soulâs activity directly.Â Epistemolois and methodological implications of the theory of perception Shadrâ this potentially to do aÂ revolution in psychology, that relives live, i.e. as a single agent â holistic in all the actions of our perception andÂ cognition